A Synthetic Approach for the Rapid Preparation of BODIPY Conjugates and their use in Imaging of Cellular Drug Uptake and Distribution - Krajcovicova, Sona; Stankova, Jarmila; Dzubak, Petr; Hajduch, Marian; Soural, Miroslav; Urban, Milan (Chemistry (Weinheim an der Bergstrasse, Germany), 2018)
A solid-phase synthetic (SPS) method was developed for the preparation of BODIPY-labeled bioactive compounds that allows for fast and simple synthesis of conjugates for use in fluorescent microscopy. The approach was used to visualize cellular uptake and distribution of cytotoxic triterpenes in cancer cells.
Keywords: Biological Transport; dyes/pigments; biologický transport; Tissue Distribution; cytotoxicity; Boron Compounds; tkáňová distribuce; fluorescenční mikroskopie; Humans; triterpeny; fluorescence microscopy; Microscopy, Fluorescence; terpenoids; Triterpenes; lidé; sloučeniny boru; solid-phase synthesis